Dragonfly Inventory and Activity in Kasang Kulim Zoo Area, Riau - Miranda Delithalia; Radith Mahatma (Bioeksperimen: Jurnal Penelitian Biologi, 2023)
Dragonflies have an important role in ecosystem balance as biological control agents and environmental bioindicators because they are sensitive to changes in water quality. Community activities at the Kasang Kulim Zoo can cause changes to water quality. When habitat conditions change, Odonata (dragonfly) will also changes, both in distribution and diversity. This study aims to identify, invent and determine the activity time of dragonflies found in the Kasang Kulim Zoo area. Research was conducted at the end of March to mid-April 2023. Sampling used exploration method by using insect nets. The results obtained a total of 152 individuals belonging to 14 species, four families and two suborders (Anisoptera and Zygoptera). The family Libellulidae totaled eight species, Gomphidae one species, Coenagrionidae four species and Platycnemididae one species. The Libellulidae family are active from 08.00 am to 05.00 pm, while dragonfly species from the Gomphidae family and the Zygoptera suborder are active from 08.00 am to 03.00 pm. Dragonfly activity is influenced by air temperature, air humidity and sunlight intensity.